Process for preparation of fish extract having pharmaceutical function - Mat Jais, Abdul Manan (2009)

(untitled)
This innovation relates to a process for preparation of fish extract. The extract produced according to the process is shown to possess pharmaceutical functions. The innovation offers a simple extraction are eliminated.